IMPLEMENTASI KEBIJAKAN PENGEMBANGAN PARIWISATA DI KABUPATEN PULAU TALIABU - Rikardo Dagasou, Riki (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2024)
Taliabu Regency has several potential or tourist destinations that can be developed and later become superior, starting from the beauty of its beaches with white sand, coral reefs which are often found in the waters, to forests that are still natural and have not even been touched by humans. This research aims to determine the implementation of tourism policy in Taliabu Regency using Edward III's analysis which includes: Communication, Resources, Disposition and Bureaucratic Structure. The research method is descriptive qualitative. The research results show that the Taliabu Tourism Service, in communicating, especially with policy target objects, consistently uses the communication channel of invitation letters whose material is socialization and discussion. The Taliabu Tourism Office is aware of the limited regional budget for tourism. These limitations then encourage the tourism department to collaborate with the community and other parties to implement policies. The attitude of policy implementers in the field is also emphasized by the Taliabu service because it is very influential in the success of policy implementation. The research findings show that the department distributes responsibility or authority both within the Tourism Department in implementing policies and coordinating between departments related to policy implementation. This cooperation and delegation of authority aims to make policy implementation successful.